2013
DOI: 10.1080/01932691.2012.713248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colloidal Dispersion of Clay on Some Properties of Wool Fiber

Abstract: This work was carried out to characterize the changes induced on wool fiber by clay treatment. Technical measurements were studied including Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermal degradation analysis (TGA), scanning electron microscopy (SEM), moisture regain measurement (MRM), and tensile strength test (TST). The intensity of major peaks in FTIR spectra of the clay treated sample is in favor of chemical changes of the polypeptide functional groups. DSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 54 publications
2
4
0
2
Order By: Relevance
“…The band at 1047 cm À1 is due to aromatic skeletal vibrations (C=C), and the band at 868 cm À1 is assigned to C-H bending vibration in the benzene ring. These results demonstrated the presence of benzene rings and hydroxyl groups of ellagic acid in the chestnut shell extract according to previous reports [11,[30][31][32]. Similar results are also observed in the FTIR spectrum of the black rice bran extract.…”
Section: Ftir Analysissupporting
confidence: 91%
“…The band at 1047 cm À1 is due to aromatic skeletal vibrations (C=C), and the band at 868 cm À1 is assigned to C-H bending vibration in the benzene ring. These results demonstrated the presence of benzene rings and hydroxyl groups of ellagic acid in the chestnut shell extract according to previous reports [11,[30][31][32]. Similar results are also observed in the FTIR spectrum of the black rice bran extract.…”
Section: Ftir Analysissupporting
confidence: 91%
“…Our group has recently demonstrated that Fe-PILC is able to reduce the high reflective index of silica and aluminum in total clay particles throughout the spectral range of 400-700 nm. 9,13,14 This reduction becomes stronger at 520 nm. The reflective curves of cotton also decrease as the surface roughness increases due to the aggregation of nanoparticles.…”
Section: P Gashti and S Eslamisupporting
confidence: 85%
“…Comparison between some mechanical properties of natural and synthetic fiber. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Fiber Density (g/cm 3 The bio-based matrix plays a parallel role as of the polymer matrix which helps to transfer applied shear load to fibers to protect them from physical damage. The categorization of biodegradable polymers and synthetic biopolymers is presented in Table 4.…”
Section: Biodegradable Polymer Matrixmentioning
confidence: 99%